2013
DOI: 10.1136/bjsports-2012-092087
|View full text |Cite
|
Sign up to set email alerts
|

The Oslo Sports Trauma Research Center questionnaire on health problems: a new approach to prospective monitoring of illness and injury in elite athletes

Abstract: The new method was sensitive and valid in documenting the pattern of acute injuries, overuse injuries and illnesses in a large, heterogeneous group of athletes preparing for the Olympic and Paralympic Games.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
579
9
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(616 citation statements)
references
References 33 publications
(34 reference statements)
25
579
9
3
Order By: Relevance
“…For example, we expected to capture a far greater number of injuries using the OSTRC Overuse Injury Questionnaire than using a time-loss-injury approach because many athletes continue to train and compete despite being injured. 9,15 However, our results are in accordance with those of Andersen et al, 16 Clarsen et al, 10,17 Jacobsson et al, 18 and Ristolainen et al, 19 demonstrating that overuse injuries are more common than acute injuries in several sports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, we expected to capture a far greater number of injuries using the OSTRC Overuse Injury Questionnaire than using a time-loss-injury approach because many athletes continue to train and compete despite being injured. 9,15 However, our results are in accordance with those of Andersen et al, 16 Clarsen et al, 10,17 Jacobsson et al, 18 and Ristolainen et al, 19 demonstrating that overuse injuries are more common than acute injuries in several sports.…”
Section: Discussionsupporting
confidence: 92%
“…The question of whether adolescent elite orienteerers should avoid participating in alternative sports cannot be answered based on our results, but our findings highlight the importance of identifying the injury circumstances. In addition to injuries, the most common cause of the inability to train fully was illness, which is in accordance with the report of Clarsen et al, 17 who observed that 36% of athletes preparing for the Olympic and Paralympic Games reported illnesses.…”
Section: Discussionsupporting
confidence: 90%
“…In sports with high proportions of overuse injuries such as cross-country, it may be beneficial to consider other models of injury surveillance. 15 …”
Section: Limitationsmentioning
confidence: 99%
“…Last, it is possible that previous researchers 12 who examined only TL injuries may have recorded the same injury every instance it caused time loss. Other authors 15 have considered examining the prevalence of injuries, including conditions causing unspecified pain. Future work should involve methods to better track overuse injuries or conditions that result in pain or functional limitations independent of TL or injury diagnosis.…”
Section: Overuse and Ntl Injuriesmentioning
confidence: 99%
“…Nonetheless, to support identification of risk factors, it will still be necessary to structure sports impairment concepts by causal mechanisms, and in particular to differentiate between discrete and enduring causal processes. Especially for documentation of sports impairment associated with overuse syndromes, the participants' self-reports of symptoms need to be included as an integral part of data collection frameworks, as has recently also been advocated by Clarsen et al [20]. Only in this way can knowledge be attained on how sensations of pain, discomfort, and loss of functioning are interpreted and related to damages to anatomical structures and physiological functions.…”
Section: Discussionmentioning
confidence: 99%